STRATEGI KOMUNIKASI PEMASARAN DALAM MEMPROMOSIKAN PRODUK MELALUI ONLINE (STUDI DESKRIPTIF KUALITATIF PADA DISTRO TOKO ONLINE “ BAHAN OKE MEDAN ” DI APLIKASI TOKOPEDIA) - Elysabeth Nahomi Simamora; Rita Vinolia Aruan (JURNAL SOCIAL OPINION: Jurnal Ilmiah Ilmu Komunikasi, 2021)
This research is entitled "Marketing Communication Strategies in Promoting Products Through Online Qualitative Descriptive Studies on online store distributions "Ok Medan material is applied to Tokopedia". This study aims at determining the concept of strategy in marketing a product through online. The research method used is qualitative with a descriptive approach. This research method provides an overview by collecting data obtained from the processes and events that occur in the object of research. In addition, researchers also conducted in-depth interviews with research subjects in order to obtain research results in accordance with the research objectives. This study contains a description of the background of observations, quotes and results from interviews to provide an overview of the presentation of the report. This theory is related to the theory of new media, communication theory, and marketing theory which is carried out by okefield materials in maximizing customer satisfaction strategies which have a very close relationship and achieve price increases in the market so as not to lose the price of the products we sell. The research was conducted at the owner's house on Jalan Serayu II no. 119, Sei Rice Sekata Medan Krio, Deli Serdang Regency, Medan. The informant interviewed was one of the owners or business owners, from the results of the research conducted there were several main points that became the results of the research, namely the proven ones taken, namely new media, communication strategies, marketing, promotions and ideas. In achieving a strategy to increase sales results in online media, especially Tokopedia. Researchers get the data from the results of interviews, observations and documentation. Based on the results of this study, it can be concluded that the communication process carried out on the Tokopedia account for materials okay Medan applies a directed communication strategy and includes communication components (source, message, media, receiver and feedback).